2013
DOI: 10.7235/hort.2013.12131
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functional Markers for Detection of Inactive DFR-A Alleles Responsible for Failure of Anthocyanin Production in Onions (Allium cepa L.)

Abstract: Abstract. Inactivation of the gene coding for dihydroflavonol 4-reductase (DFR) is responsible for the color difference between red and yellow onions (Allium cepa L.). Two inactive DFR-A alleles, DFR-A PS and DFR-A DEL , were identified in our previous study. A functional marker was developed on the basis of the premature stop codon that inactivated the DFR-A PS allele. A derived cleaved amplified polymorphic sequences (dCAPS) primer was designed to detect the single nucleotide polymorphism, an A/T transition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Furthermore, RT-PCR results showed that no DFR-A transcript was detected in any yellow F 2 individuals. Further, Park et al (2013b) …”
Section: Molecular Markers For Colour Improvement In Onionmentioning
confidence: 95%
“…Furthermore, RT-PCR results showed that no DFR-A transcript was detected in any yellow F 2 individuals. Further, Park et al (2013b) …”
Section: Molecular Markers For Colour Improvement In Onionmentioning
confidence: 95%
“…Four alleles encoding anthocyanidin synthase (ANS) have been proposed to condition red, pink and yellow colour in bulbs (Kim et al 2006). DFR and ANS mapped on chromosomes 7 and 4, respectively, and functional markers from these candidates have been developed, which could be used in marker-assisted selection for bulb colour (Masuzaki et al 2006, Khar et al 2008, Kim et al 2009, Park et al 2013, Duangjit et al 2014.…”
Section: Bulb Colourmentioning
confidence: 99%
“…1 positive control containing the functional DFR-A R1 allele, 2 430C, 3 PI276324, 4 control containing the DFR-A DEL allele in which the entire DFR-A gene was deleted. The 898-bp PCR products amplified using the primer combinations of DFR-DEL-F, DFR-DEL-R1, and DFR-DEL-R2 were amplified from the DFR-B gene, an inactive pseudogene (Park et al 2013) (DFR-LF1 and DFR-DEL-R1) binding to the 5′ and 3′ flanking sequences of the DFR-A gene (Fig. 1a), resulting in the amplification of single large-sized PCR products in both accessions ( Supplementary Fig.…”
Section: Identification Of Three Dfr-a Alleles Containing Tesmentioning
confidence: 99%